Ending preventable maternal deaths in Malawi: the stakeholders consensus approach to identify maternal health needs priorities - Mtisunge Joshua Gondwe; Leonard Mndala; Chifundo Kondoni; Annie Kuyere Khumalo; Bertha Maseko; Laura Munthali; Catherine Bamuya; Rosemary Bilesi; Henry Phiri; Fannie Kachale; Malangizo Mbewe; Jennifer Riches; et al. (BMC Health Services Research)
Abstract Background The Malawian context presents multifactorial challenges that hinder the provision of high-quality maternal health services, leading to high maternal morbidity and mortality rates. Priority setting is a crucial concept that can benefit the healthcare system in Malawi by efficiently distributing limited resources and maximising gains in maternal healthcare. We undertook a national maternal health prioritisation exercise involving key stakeholders to enhance delivery of maternal care in Malawi. Methods During group discussions, the Nominal Group Technique was adapted to facilitate consensus on priorities after data and real-life experiences from service users were presented. The process involved four stages: (1) Silent generation of priorities, where participants independently listed their priorities using pieces of paper, (2) Consolidation of priorities, where all individual priorities were combined into a single list on the flip chart and similar priorities merged, (3) Clarification and discussion at a group level using a prioritisation matrix, allowing participants to clarify and discuss the listed priorities, and (4) Ranking of generated priorities, where participants voted or used an online scoring system to determine the most important priorities. All papers and flip charts used were collected, and discussions were recorded to capture how decisions were made, and their rationales. Facilitators and authors met to manually analyse the summaries. Results Seventy-four stakeholders participated in the prioritisation workshop, forming eight groups. Through individual prioritisation exercises, 233 priorities were identified. Subsequently, the consolidation of priorities resulted in 104 priorities, which were further reduced to 40 priorities during clarification and discussion stage using the prioritisation matrix. After selecting the top two priorities from each group, 12 priorities remained, which underwent the final stage of ranking and voting, and 57 stakeholders voted. The top three priorities identified were: (1) respectful maternity care, (2) information and data management, and (3) strengthening skills of birth attendants. Conclusion Achieving national maternal health targets demands prioritising respectful maternity care, accessible information, robust data management/information, and skilled birth attendants, all of which empower staff and clients to drive positive changes. Stakeholders can leverage these priorities to guide future programme implementation, research investments, and country-specific adaptations through meaningful engagement with national stakeholders.